Assessment of Population Perception Impact on Value-Added Solid Waste Disposal in Developing Countries, a Case Study of Port Harcourt City, Nigeria - Adekunle, Iheoma Mary; Oguns, Oke; Shekwolo, Philip D.; Igbuku, Augustine O. O.; Ogunkoya, Olayinka O. (IntechOpen, 2012)
None